NLRP3 deficiency ameliorates renal inflammation and fibrosis in diabetic mice. (15th December 2018) - Wu, Ming; Han, Weixia; Song, Shan; Du, Yunxia; Liu, Chao; Chen, Nan; Wu, Haijiang; Shi, Yonghong; Duan, Huijun
Abstract: Diabetic nephropathy (DN) is the leading cause of end-stage renal disease. Activation of the nucleotide binding and oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome has been reported in diabetic kidney, yet the potential role of NLRP3 inflammasome in DN is not well known. In this study, we explored the role of NLRP3 inflammasome on inflammation and fibrosis in diabetic kidney using NLRP3 knockout mice. Renal expression of NLRP3, caspase-1 p10, interleukin-18 (IL-18) and cleaved IL-1β was increased in diabetic wild-type (WT) mice at 24 weeks. NLRP3 knockout (KO) improved renal function, attenuated glomerular hypertrophy, glomerulosclerosis, mesangial expansion, interstitial fibrosis, inflammation and expression of TGF-β1 and connective tissue growth factor (CTGF), as well as the activation of Smad3 in kidneys of STZ-induced diabetic mice. In addition, NLRP3 KO inhibited expression of thioredoxin-interacting protein (TXNIP) and NADPH oxidase 4 (Nox4) and superoxide production in diabetic kidneys. The diabetes-induced increase in urinary level of 8-hydroxydeoxyguanosine (8-OHdG) was attenuated in NLRP3 KO mice. In vitro experiments, using HK-2 cells, revealed that high glucose (HG)-mediated expression of TXNIP and Nox4 was inhibited by transfection with NLRP3 shRNA plasmid or antioxidant tempol treatment. Silencing of the NLRP3 resulted in reduced generation of reactive oxygen species (ROS) in HK-2 cells under HG conditions. Furthermore, we also found exposure of IL-1β to HK-2 cells induced ROS generation and expression of TXNIP and Nox4. Taken together, inhibition of NLRP3 inflammasome activation inhibits renal inflammation and fibrosis at least in part via suppression of oxidative stress in diabetic nephropathy. Highlights: NLRP3 deletion improves renal function in diabetic mice. NLRP3 KO attenuates inflammation and fibrosis in diabetic kidney. NLRP3 deficiency reduces oxidative stress in diabetic nephropathy. NLRP3 deficiency inhibits TXNIP expression in diabetic nephropathy.